PENGARUH IKLAN MELALUI MEDIA TELEVISI DAN WOM TERHADAP MINAT BELI KONSUMEN PADA PRODUK UNIT LINK - FITRIA C M, MAWIDHA (Jurnal Ilmu Manajemen (JIM), 2016)
This study aimed to analyze and discuss the influence of advertising through television media and word of mouth (WOM) for consumer purchase interest in unit-linked products PT. AXA Financial Indonesia. This type of research is quantitative. This study uses the respondents who have never become customers of PT. AXA Financial Indonesia. Techniques nonprobability sampling with 100 respondents. Data analysis techniques using PAWS Statistics 18 Software. Result of the research shows that advertising through television media and word of mouth (WOM) has a positive influence on interest in the purchase. Keyword: advertising, word of mouth (WOM), and purchase attention.